2019
DOI: 10.1016/j.arcontrol.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A controller perspective on biological gait control: Reflexes and central pattern generators

Abstract: Biological motion control paradigms can be analyzed from a control theory point of view and translated to control applications. This paper revises and updates important aspects about the neural control of biped gait based on the Central Pattern Generator (CPG) and provides a controller view, including possible artificial implementations of these controllers. A first aspect to consider is the biological sensor-actuation system because the particularities of this system: the mammalian muscle. Many current biped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 121 publications
(143 reference statements)
0
10
0
Order By: Relevance
“…The autonomously generated signal can be combined with the control signal from the higher centre to generate gait movements. 12,13 In a previous study, 14 we found a specific CPG site on the right side of the rat spinal cord. In particular, rats can be induced to move the left hindlimb flexion and the right hindlimb extension by stimulating this site with positive pulses, while negative-pulse stimulation induces the opposite motion.…”
Section: Introductionmentioning
confidence: 71%
“…The autonomously generated signal can be combined with the control signal from the higher centre to generate gait movements. 12,13 In a previous study, 14 we found a specific CPG site on the right side of the rat spinal cord. In particular, rats can be induced to move the left hindlimb flexion and the right hindlimb extension by stimulating this site with positive pulses, while negative-pulse stimulation induces the opposite motion.…”
Section: Introductionmentioning
confidence: 71%
“…A central pattern generator (Torrealba et al 2012;Torrealba et al 2010;Guo et al 2010;Duysens and Forner-Cordero 2019) uses biologic neural grid. They are modulated by basic sensory signals which are being modeled and extensively studied.…”
Section: Resultsmentioning
confidence: 99%
“…Impedance control algorithm (Varol and Goldfarb 2007;Herr and Wilkenfeld 2003;Duysens and Forner-Cordero 2019) is the most commonly used control strategy (El-Sayed et al 2014) within which the torque generated is tailored to the produced knee angle. It ensures that the knee joint produces sufficient torque that is worthy for every phase of gait (Martinez-Villalpando and Herr 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The correlation between the stimulus signal voltage amplitude and gait angle data is converted into a mapping relationship. The CPG site was stimulated by pressing the button to change the voltage amplitude of the stimulus signal, and the knee joint angle of the unilateral hindlimb was measured to establish the knee joint angle and signal parameter model [21][22][23].…”
Section: Amplitude-angle Modelmentioning
confidence: 99%